An Analysis of Children's Literature to Develop Reading Skills in Elementary Students Enrolled in International Programs - Bunjongtaem, Pimchanok; Sumalee, Sittikorn; Koolsriroj, Udomluk (Journal of MCU Phetchaburi Review, 2025)
The objectives of this study were: 1) to analyze children's literature for the developing reading skills in elementary students enrolled in international programs. 2) to evaluate the results of an analysis of children's literature for the development of reading skills in elementary students enrolled in international programs. The samples for this study consisted of 10 children's literature books, both fiction and non-fiction, that had been awarded the outstanding book award from the office of the basic education commission, ministry of education. These books were published between 2021 and 2024 and were selected through purposive sampling. They were evaluated by 5 experts in Thai language education for their appropriateness, resulting in 8 literary works deemed suitable for the elementary students. The study findings showed that: 1) Children's literature reflects significant social issues in Thai society, covering topics such as nature and environmental conservation, daily life, family relationships, the preservation of Thai traditions and culture, and life philosophy. The language used in 6 books was semi-formal, with simple and easily comprehensible expressions, while 2 books employed more complex language, requiring readers to interpret and analyze the content in depth. The application of these literary works in teaching can effectively support the development of all aspects of Thai language skills. 2) Children's literature was deemed highly appropriate to develop reading skills in elementary students enrolled in international programs, with its suitability rated at a high to very high level.